Testing techniques for silty sands and pond ash: focus on instability and critical state - Baki, Md Abdul Lahil; Rahman, Md. Mizanur; Lo, S. R.; Abrar, Md Mahi (Geotechnical research, 2025)
Triaxial apparatus is a commonly adopted testing device for understanding the mechanical behaviours of soils from laboratory tests. The uniform distribution of stress–strain inside the specimen till a large strain close to a steady state is a challenge. Over nearly three decades, research at the University of New South Wales, Canberra, has led to notable improvements in triaxial testing techniques. This article reviews both standard and advanced triaxial testing techniques. These include the ability of the triaxial testing device to measure and record instability behaviour, specimen preparation techniques, enlarged platens with free ends, and its effects, accuracy, and errors involved in the different measurements/calculations. A total of 166 critical state data points of Sydney sand with fines and pond ash prepared under different specimen methods and testing conditions have been included to evaluate the effectiveness and reliability of the abovementioned techniques. Representative monotonic and cyclic test results have been presented to further validate the techniques. The results demonstrate that a unique critical state line can be reliably established, enabling the accurate estimation of state parameters to predict instability behaviour using the critical state soil mechanics framework under both static and cyclic loading conditions.